A PEEK INTO MEDICAL STUDENTS’ PERCEPTIONS TOWARDS LEARNING ENVIRONMENT IN BASIC MEDICAL SCIENCES BLOCK - Saphira Nada Khalishah; Ziske Maritska; Joko Marwoto (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Biology is one of the cornerstones of studying medicine. It is imperative for medical students to get a grasp of it before further proceed to advanced medical sciences. Learning and comprehending the subject will help medical students further in their studies. The learning environment is one of the major factors that determine the success of a learning process. This study aimed to assess student’s perception of the learning environment on the biology medicine block, as one of the basic medical sciences blocks given in the first semester in the Faculty of Medicine, Universitas Sriwijaya.Methods: A descriptive observational study with a cross-sectional design on 221 second-year medical students that have undergone the biology medicine block. Assessment is done using Dundee Ready Education Environment Measure (DREEM) questionnaire.Results: A total of 221 respondents, 67.4% have a good perception of learning, a very good perception of lecturers 115 respondents (52%), a good academic achievement of 62%, a perception of a good learning atmosphere is 72% and a perception of a good environment is 73.8%.Conclusion: The majority of respondents stated good perception among all categories.